Compare the Clinical Severity and Length of Hospital Stay in Children with Bronchiolitis Treated with the 3% Hypertonic Saline Nebulization Versus Normal Saline and Salbutamol - Omparkash, Amanullah Lail, Taj Muhammad Laghari, Sirichand, Mushtaque Ali Shah, Muhammad Aslam Chandio (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Acute bronchiolitis, a lower respiratory tract infection, is the most common reason for hospitalizing infants and children for breathing issues. Salbutamol dissolved in sterile saline solution was commonly used to treat hospitalized infants with acute bronchiolitis. This study was conducted with the hypothesis that giving bronchiolitis-affected infants 3 % hypertonic saline solution to inhale instead of 0.9% NS+salbutamol would reduce their clinical severity ratings and length of hospitalization. Objective: To compare the clinical severity and length of hospital stay in children with bronchiolitis treated with the 3% hypertonic saline nebulization versus Normal saline and salbutamol Study Design: A randomized controlled trial Place and Duration: This study was conducted at Indus Medical College The University of Modern Sciences, Tando Muhammad Khan from June 2021 to June 2022 Methodology: A total of 120 individuals with acute bronchiolitis were included in this research after exclusions and inclusions. Both the 0.9% normal saline with salbutamol nebulization and the 3% hypertonic saline nebulization (n = 60) were randomly assigned to the two groups. The data was obtained regarding, age, gender, the pattern of presentation, clinical severity at different time intervals, duration of oxygen therapy, length of hospital stay, and rapid or gradual improvement and discharge of the patient from the hospital. Chi-square and unpaired t-tests were employed as test statistics to analyse the categorical data numerical data. The level of significance was set at 5%, with p0.05 (at the 95% confidence interval) being regarded as significant. Results: A total of 32 (53.3%) females made up group I, while 34 (56.67%) males made up group II. In groups I and II, the mean hospital stays were respectively 61.7±14.5 hours and 81.4±18.2 hours. The mean and standard deviation for group I oxygen therapy time was 13.5± 4.2, while group II was 23.8±4.9 hours. Amongst the hypertonic saline group, out of total 60 patients, 55 (91.67%)patients were recovered and discharged rapidly. Meanwhile, in group II, 32 (53.3%) patients were recovered and discharged rapidly. Conclusion: Yet, in terms of symptom relief, oxygenation improvement, and length of hospital stay for a baby with acute bronchiolitis, the 3% hypertonic saline group outperformed the 0.9% normal saline group. Clear clinical improvements and an increase in oxygen saturation were seen in both therapy groups. Keywords: Acute Bronchiolitis, Hypertonic Saline, Normal Saline, Salbutamol